The challenges of treating tracheobronchitis in a laryngectomee due to nontypeable Haemophilus influenzae: a case report - Brook, Itzhak (J Med Case Rep, 2018)
BACKGROUND: Laryngectomees run the risk of developing severe respiratory tract infections especially during the winter and when they do not wear a stoma cover. A case of severe tracheobronchitis in a laryngectomee is presented that illustrates the risks and difficulties encountered in managing this infection in a neck breather. CASE PRESENTATION: A 76-year-old Caucasian man, a laryngectomee, presented with bacterial tracheobronchitis and conjunctivitis due to beta-lactamase-producing nontypeable Haemophilus influenzae. He was febrile (38.9 °C; 102.0 F), and had repeated episodes of hypertension. He was treated with levofloxacin 500 mg/day, ciprofloxacin eye drops, acetaminophen, and guaifenesin. Humidification of his trachea and the airway was sustained by insertions of saline into the stoma as well as breathing humidified air. The main challenge was to maintain the patency of his airway as the mucus was very dry and viscous and tended to stick to the walls of his trachea and the stoma. His condition improved within 7 days and he had a complete recovery. CONCLUSIONS: Maintaining the patency of the airway in laryngectomees who suffer from lower respiratory tract infection is of utmost importance as the mucus can be very dry and viscous and can stick to the walls of the trachea and the stoma.